2008
DOI: 10.1177/0011128707308216
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Error in Household Gun Ownership in the 2000 General Social Survey

Abstract: The use of surveys

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… 9 When the coefficients of a logistic regression are transformed through a simple formula, we may interpret the result as a percentage change in odds of the dependent variable for a one-unit change on the independent variable while holding all other variables constant (Legault, 2008: 85). …”
mentioning
confidence: 99%
“… 9 When the coefficients of a logistic regression are transformed through a simple formula, we may interpret the result as a percentage change in odds of the dependent variable for a one-unit change on the independent variable while holding all other variables constant (Legault, 2008: 85). …”
mentioning
confidence: 99%
“…Mays and Ruddell (2002), for instance, found that Canada Firearm Centre estimates of Canadian gun ownership were likely to be underestimates. Existing research in the U.S. found significant reporting discrepancies within married couples in the General Social Survey; married women were less likely to report household gun ownership than their male partners (Legault, 2008). The authors attributed this discrepancy to social undesirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this discrepancy to social undesirability bias. Interestingly, the gap between male and female reporting was lessened in areas of the U.S. with a stronger gun culture, suggesting some cultural influence related to social acceptance of gun ownership (Legault, 2008). Future research may be able to better identify the acceptability of guns in cultures across the world.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that families of boys with single mothers were likely to have substantial reporting error between household members, while other family arrangements were associated with more consistency of firearms ownership reporting (Sorenson and Cook, 2008). Another piece of research found significantly divergent patterns in firearm ownership reporting between married couples, inferring a social desirability suppression effect among women respondents, especially outside “areas with traditional gun culture” (Legault, 2013). A group of criminologists sought to evaluate how the college survey’s method structured responses to questions about guns and gun policy, and found that the in‐class method had a much higher level of non‐response and was systematically exclusive of more controversial and “extreme positions” on guns and gun policy (Wells, Cavanaugh, Bouffard, and Nobles, 2012).…”
Section: Relevant Literaturesmentioning
confidence: 99%